NEUROPEPTIDE S100-b: THE DIAGNOSIS OF A MALIGNANT CEREBROVASCULAR ACCIDENT - T. Yu. Shaytanova; V. A. Saskin; E. V. Nedashkovsky (Вестник анестезиологии и реаниматологии, 2017)
The major heart attack in the carotid system, going with the cerebral edema is considered to date as the most mortal type of the ischemic stroke. The only prove successful treatment policy is the decompressive craniectomy. The early start of the operative intervention, reported in the references, brings about improvement of the clinical outcomes, however under limited time the diagnostics issues remain open and, as a consequence there perform the unreasonable traumatic operational assistance. 43 patients with the severe ischemic stroke were examined and an analysis of the S100-b glial peptide as a marker of malignant brain infarction course was performed. The neuropeptide monitoring in the blood serum allows detection of the responders to the decompressive craniectomy among the high-risk patients within 12-16 hours of the disease onset till the clinical deterioration development, when according to the computerized tomography the certain changes have not in yet.